Clinical, genomic and immune microenvironmental determinants of nivolumab response in head and neck squamous cell carcinoma - Tsujikawa, Takahiro; Ohno, Kazuchika; Morita, Kei-ichi; Saburi, Sumiyo; Mitsuda, Junichi; Yoshimura, Kanako; Kimura, Alisa; Morimoto, Hiroki; Ogi, Hiroshi; Shibata, Saya; Akashi, Takumi; Kurata, Morito; et al. (Frontiers in Immunology, 2024)
In view of improving biomarkers predicting the efficacy of immunotherapy for head and neck squamous cell carcinoma (R/M HNSCC), this multicenter retrospective study aimed to identify clinical, tumor microenvironmental, and genomic factors that are related to therapeutic response to the anti-PD-1 antibody, nivolumab, in patients with R/M HNSCC. The study compared 53 responders and 47 non-responders, analyzing formalin-fixed paraffin-embedded samples using 14-marker multiplex immunohistochemistry and targeted gene sequencing. Of 100 patients included, responders had significantly lower smoking and alcohol index, higher incidence of immune related adverse events, and higher PD-L1 expression in immune cells as well as PD-L1 combined positive score (CPS) than non-responders. The frequency of natural killer cells was associated with nivolumab response in patients with prior cetuximab use, but not in cetuximab-naïve status. Age-stratified analysis showed nivolumab response was linked to high CPS and lymphoid-inflamed profiles in patients aged ≥ 65. In contrast, lower NLR in peripheral blood counts was associated with response in patients aged < 65. Notably, TP53 mutation-positive group had lower CPS and T cell densities, suggesting an immune-excluded microenvironment. Patients with altered tumor suppressor gene pathways, including TP53, CDKN2A, and SMAD4 mutations, had lower CPS, higher smoking index, and were associated with poor responses. These findings indicate that nivolumab treatment efficacy in HNSCC is influenced by a combination of clinical factors, age, prior treatment, immune environmental characteristics, and gene mutation profiles.